دراسة بيئية لرخويات وسط مائي عذب (نهر الأبرش) في المنطقة الساحلية السورية - كروم محمود; ياسين قصاب محمد; فاضل اقبال (Latakia University Journal -Basic Sciences Series, 2018)
لقد تمت دراسة وسط مائي عذب (نهر الأبرش) في المنطقة الساحلية السورية، من حيث صفاته اللاحيوية (الصفات الفيزيائية الكيميائية للوسط خاصةً) والحيوية، وذلك من تاريخ 12/3/1999 وحتى 12/1/2001. تتصف مياه النهر بدرجات حرارتها المرتفعة صيفاً والمنخفضة شتاءً وغناها النسبي بالأوكسجين وبشوارد الكلور وبطبيعتها الكلسية. لقد تم التعرف على 13 نوعاً من الرخويات منها 12 نوعاً من صف بطنيات القدم Gastropoda (9 أنواع من تحت صف أماميات الغلاصم Prosobranchia و3 أنواع من تحت صف الرئويات Pulmonata)، ونوع واحد من صف ثنائية المصراع Bivalvia. لقد تمت دراسة أحد الأنواع الرخوية الغزيرة وهو النوع Hydrobia sp. في الوسط من حيث بنية جماعته. وتم إيجاد العلاقة بين النمو الطولي للقوقعة والنمو العرضي، وكذلك العلاقة بين النمو الطولي للقوقعة ووزنها الجاف. كما تمت دراسة حركية الجماعة التي أظهرت أن التكاثر مستمر لهذا النوع طيلة العام مع وجود فترتين واضحتين من النشاط التكاثري: الأولى ربيعية طويلة والثانية خريفية قصيرة نسبياً كما أن العمر المتوسط للفرد يقدر بحوالي 12 شهر . A fresh water site (Al-Abrash river) of the Syrian coastal region was studied for the biotic and abiotic properties (esp. the physical & chemical properties), during the period 12/3/1999 till 12/1/2001. The water of the river is characterized by high water temperature during summer times, and by low water temperature during winter times, together with relatively high oxygen and Chloride levels and by the calcareous nature. Thirteen mollusks species were identified; one belonging to Bivalvia and twelve others belonging to Gastropods ( i.e. nine from Prosobranchia and three from Pulmonata). Population structure of the most abundant mollusk species (i.e. Hydrobia sp.) was studied. The relation between the longitudinal growth & the cross growth, together with the relation between the longitudinal growth & and the dry weight of the shell were estimated. The study on population dynamic was revealed that the reproduction process of this species continues throughout the year with two periods of the reproduction activity: the first is during spring and the second is during fall. The average age of this species is estimated to be 12 months.